Benefit of adjuvant chemotherapy in patients with lobular breast cancer: A systematic review of the literature and metanalysis. (June 2021) - Trapani, D.; Gandini, S.; Corti, C.; Crimini, E.; Bellerba, F.; Minchella, I.; Criscitiello, C.; Tarantino, P.; Curigliano, G.
Highlights: We explored the role of adjuvant chemotherapy in the treatment of patients with localized lobular breast cancer (ILC)? In this systematic review of the literature and metanalysis, a role of the adjuvant chemotherapy in the setting of ILC was not confirmed. The analysis on 38, 387 patients across 8 studies did not show an additional benefit of chemotherapy (Hazard Ratio for Overall Survival: 0.99; 95%CI 0.86–1.14). However, all the investigations were retrospective, and subgroup analyses in high-risk patients showed some signals of possible adjunctive benefits. Prospective investigations of adjuvant therapies in high-risk patients with ILC are highly warranted. The current decision- making is largely based on evidence from non-randomized clinical investigations, prompting controlled clinical studies. Abstract: The role of adjuvant chemotherapy (aCT) for patients with localized lobular breast cancer (ILC) is still controversial. It is unclear what is the magnitude of benefit of the CT in this setting. In this systematic review of the literature and metanalysis, we aimed to estimate the benefit of aCT in addition to the standard treatments in the early ILC setting. We identified the records by searching Medline, CENTRAL, Web of Science, SCOPUS, and Google Scholar, and the meeting proceeding of the principal oncology meetings of the last 10 years, with no language or time restriction. A research strategy was developed with mapped and MeSH terms. Studies on the clinical use of aCT reporting survival outcomes in the ILC setting were double-screened and tabulated. PRISMA methodology was used for data extraction and synthesis. We extracted information on the study design and setting, eligible population and population size, histology variants, menopausal status, treatment regimens, follow-up duration. Hazard ratios (HR) and 95% confidence interval (CI) were extracted and transformed into logHR and corresponding standard error to obtain the Summary HR (SHR). Heterogeneity (I 2 statistics) and publication bias (Macaskill test) were tested; a random effect models provided by SAS Proc Mixed was used for data analysis. Sensitivity analysis was conducted to examine the impact of inclusion criteria on the summary results. Disease-free (DFS), overall (OS) and cancer-specific survival (BCSS) were the primary endpoints of the investigation. The systematic review and metanalysis included 38, 387 patients across 8 clinical studies. aCT was not associated with an improvement of OS (SHR 0.99; 95%CI 0.86–1.14), with low heterogeneity (I 2 = 28%) and no publication bias (p = 0.43). Sensitivity analysis resulted in unchanged conclusions. We did not perform a metanalysis of the DFS estimates, as only reported in 3 studies. The value of aCT in improving DFS was unconfirmed, consistently with the OS results. Our research did not confirm a certain role of aCT for patients with ILC. Research gaps were identified, warranting the development of prospective, controlled ad hoc investigations.